Study of the possibility of transfer of esa-12 electron spectrometer of double pass cylindrical mirror type into a spectrograph mode - Saulebekov, A.O.; Assylbekova, S.N.; Kambarova, Zh.T.; Tussupbekova, A.K. (Publishing House of the KarSU named after E.A.Buketov, 2012)
In the article, the possibility of transfer of ESA-12 electron spectrometer double pass cylindrical mirror type into a spectrograph mode is studied. The obtained modernized scheme is the design on the basis of three coaxial cylinders with the "axis-axis" focusing, which is able to operate in the spectrograph mode. The modeling of electron-optical scheme of the modified energy analyzer by means the numerical program "Focus" for modeling the corpuscular optics systems is conducted. It is noted, that when using the proposed scheme can significantly increase the accuracy and rapidity of investigations of the angular and energy distributions of charged particles beams
Keywords: electron spectroscopy; cylindrical mirror; energy analyzer; spectrograph; angular focusing; modeling of an electron-optical scheme